Flora's very windy day - Birdsall, Jeanne (Clarion Books, 2010)
When a big wind blows her annoying little brother away, Flora decides to save him despite the many tempting offers she gets for him from, among others, a cloud, an eagle, the man in the moon, and the wind itself.